Dietary habits of type 2 Diabetes patients: Frequency and diversity of nutrition intake - Kingdom of Saudi Arabia - Sami, Waqas; Alabdulwahhab, Khalid M.; Mohd Rashid, Ab Hamid; Alasbali, Tariq A.; Al Alwadani, Fahd; Mohammad Shakil, Ahmad (Mattioli 1885, 2020)
One of the important cornerstones of diabetes care is dietary management which should be based on healthy eating in context of food choices, cultural and social aspects. There is scarcity of literature adressing the dietary habits of type 2 diabetics in the Kingdom of Saudi Arabia (KSA). In Gulf countries, especially KSA there are ineffective dietary habits programs that can prevent and control complications from diet-relat-ed non-communicable diseases like diabetes The present study was conducted to examine the dietary habits and food frequencies of type 2 diabetes patients attending the primary healthcare centers in Almajmaah City, KSA. It was an analytical cross-sectional study by design which was conducted from February – April 2017. A self-prepared Food Frequency Questionnaire (FFQ) in English language was used to collect the data from 350 patients. The FFQ comprised of local food items that were distributed in 9 food groups. The selection of patients was done by means of systematic random sampling technique. The median age of the patients was 45 years. When compared with the food guide pyramid, the consumption of lipids and fats, sweets and bak-ery, drinks and, soups and sauces were more than the recommended intake (p<0.001) respectively. Whereas, consumption of proteins, carbohydrates, dairy products, fruits, and vegetables was less than the recommended intake (p<0.001) respectively. The dietary habits of type 2 diabetics have been reported to be poor. Individu-alizing the nutrition interventions and encouraging to change the behavior can help the patients in accom-plishing the health goals. The treating doctors should also identify the barriers that are hindering the patients from not following the recommended dietary guidelines. To achieve best results from self-care management, patients, doctors, and dietitians should work together.